A high-stability weighing paper/polytetrafluoroethylene-based triboelectric nanogenerator for self-powered In2O3 nanocubes/SnS2 nanoflower NO2 gas sensors. Issue 25 (16th June 2021) - Yang, Yan; Zhang, Dongzhi; Wang, Dongyue; Xu, Zhenyuan; Zhang, Jianhua
Abstract : This paper reviews experimental devices and results of a self-powered NO2 sensor. Abstract : The application of low-powered, sustainable sensors to detect the leak of toxic gases in factories has gradually become a future trend. In our work, we proposed a NO2 gas sensor based on an In2 O3 /SnS2 composite powered by a high-stability triboelectric nanogenerator (TENG), where weighing paper and a polytetrafluoroethylene (PTFE) film were used as friction materials. The peak-to-peak voltage of the TENG can reach stable 600 V and the output power can up to 13 mW, which exhibits superior performance. The TENG can power small portable electronic devices such as 50 LEDs and calculators. The TENG is directly connected in series with a chemoresistive gas sensor to form a TENG-driven nitrogen dioxide sensor (TENS) for the spontaneous detection of the concentration of NO2 . The sensor exhibits a high response (∼15) and rapid response/recovery time (45 s/147 s) towards 50 ppm NO2 at 43% RH and room temperature of 25 °C. Finally, a self-powered alarm system based on the TENS has been developed to monitor the concentration of NO2 in the surrounding environment. This work not only broadens the application field of the TENG as a self-powered gas sensor, but also meets the requirements of industrial IoT technology for miniaturized, low-powered, and maintainable sensors.